Implementation of The Behavioral Ivan Pavlov Conservation Theory with Modeling Techniques on Lesson Study Setting to Improve Self Achievement Students of The XI Class of Ibb SMA Lab Undiksha - Dimas Azhar; Kadek Suranata; Iketut Dharsana (International Conference on Technology and Educational Science)
This study aims to determine the application of behavioral counseling with modeling techniques to improve something well done and students will succeed through eleven lesson study class. This type of research is quasi-experimental with pre-test and post-test control groups. A sample of 22 students with df 21. The method of collecting data using questionnaires completed things well and students will succeed are 30 items. The results of the data analysis are the values of tcount 4,971 and ttable1,720 with (4,971 > 1,720) so that Ho is rejected and Ha is accepted. So there is a significant difference. It was concluded that behavioral counseling with modeling techniques to improve things well and will succeed students